Studies on the Neutralizing Effects of Protamine on Unfractionated and Low Molecular Weight Heparin (Fragmin®) at the Site of Activation of the Coagulation System in Man - Wolzt, Michael; Weltermann, Ansgar; Nieszpaur-Los, Malgorzata; Schneider, Barbara; Fassolt, Anita; Lechner, Klaus; Eichler, Hans-Georg; Kyrle, Paul A (Thrombosis and Haemostasis, 1995)
In a double-blind, randomized, cross-over study the neutralizing action of protamine towards unfractionated heparin (UFH, 150 U/kg i.v.) and a low molecular weight heparin (LMWH, Fragmin®, 100 anti-Xa U/kg i.v.) was investigated in 15 healthy subjects in vitro by measuring activated partial thromboplastin time (APTT), thrombin time (TT) and anti factor Xa activity (anti-Xa) in venous blood and in vivo by determination of prothrombin fragment 1.2 (f1.2) and thrombin-antithrombin III complexes (TAT) in venous blood and in shed blood. UFH and LMWH caused a prolongation of APTT and TT, an increase in anti-Xa and significantly inhibited f1.2 and TAT formation in shed blood, whereas only a minimal effect on TAT and f1.2 formation in venous blood was noted. Administration of 1 mg protamine/100 U UFH resulted in a near complete reversal of APTT, TT and anti-Xa, whereas lower doses (0.25 and 0.5 mg) were less effective. The effects of UFH on f1.2 and TAT generation in shed blood were partially (60-70%) neutralized only by the high dose (1.0 mg). Application of 1 mg protamine/100 anti-Xa U LMWH caused a near complete reversal of both APTT and TT but had only a weak effect on anti-Xa. In shed blood, the effect of LMWH on TAT and f1.2 formation was reversed by protamine only by 14% and 23% respectively. Our data do not support the concept that to reduce the incidence of protamine’s potential clinical side effects, the administration of a lower dose of protamine than 1 mg protamine/100 U UFH is justified. Furthermore, a significant residual impairment of hemostasis is still detectable after administration of the recommended dose of protamine to neutralize the anticoagulant effects of a LMWH preparation.